1998
DOI: 10.1073/pnas.95.21.12129
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Ets-1 pointed domain and mitogen-activated protein kinase phosphorylation site

Abstract: The Pointed (PNT) domain and an adjacent mitogen-activated protein (MAP) kinase phosphorylation site are defined by sequence conservation among a subset of ets transcription factors and are implicated in two regulatory strategies, protein interactions and posttranslational modifications, respectively. By using NMR, we have determined the structure of a 110-residue fragment of murine Ets-1 that includes the PNT domain and MAP kinase site. The Ets-1 PNT domain forms a monomeric five-helix bundle. The architectur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
142
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(150 citation statements)
references
References 34 publications
8
142
0
Order By: Relevance
“…Ets-1 transcriptional activity is known to be regulated by phosphorylation via RAS and Ca 2 þ -dependent protein kinase pathways (Rabault and Ghysdael, 1994;Rabault et al, 1996;Wasylyk et al, 1997;Slupsky et al, 1998;Cowley and Graves, 2000;Paumelle et al, 2002). Here, we demonstrated that Ets-1 is also modified by other post-translational modifications, that is sumoylation and ubiquitinylation.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Ets-1 transcriptional activity is known to be regulated by phosphorylation via RAS and Ca 2 þ -dependent protein kinase pathways (Rabault and Ghysdael, 1994;Rabault et al, 1996;Wasylyk et al, 1997;Slupsky et al, 1998;Cowley and Graves, 2000;Paumelle et al, 2002). Here, we demonstrated that Ets-1 is also modified by other post-translational modifications, that is sumoylation and ubiquitinylation.…”
Section: Discussionsupporting
confidence: 53%
“…The N-terminal sequence of Ets-1 is phosphorylated at threonine 38, within a MAPK phosphorylation motif activated following RAS activation. This phosphorylation enhances Ets-1 transcriptional activity (Rabault et al, 1996;Wasylyk et al, 1997;Slupsky et al, 1998;Paumelle et al, 2002). In particular, we demonstrated that such activation of Ets-1 is triggered by hepatocyte growth factor/scatter factor (HGF/SF) through a RAS-ERK pathway, leading to transcriptional activation of Ets-1 and activation of promoters containing RAS-Responsive Elements constituted by combined EBS/AP1-binding sites (Fafeur et al, 1997;Paumelle et al, 2002).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Our ®ndings thus suggest that the pointed/B domain homophilic interaction is a candidate target for drug development. In this context, the recently reported structures of the pointed/B domain of Ets-1, and of the structurally related SAM domains of the Eph4A and EphB2 receptor tyrosine kinases, are of great interest (Slupsky et al, 1998, Stapleton et al, 1999Thanos et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…ets-1, ets-2,¯i-1, TEL, GABPa, and ELF3, share a homologous region at the N-terminus, referred to as the pointed domain. This domain appears to be important for the transcriptional regulatory mechanisms mediated by these ets factors and might be involved in protein ± protein interactions (Slupsky et al, 1998;Oettgen et al, 1999).…”
Section: Introductionmentioning
confidence: 99%